2006
DOI: 10.1177/0002764206289654
|View full text |Cite
|
Sign up to set email alerts
|

“But they claimed to be police, not la migra!”

Abstract: In Chambersburg, a neighborhood in Trenton, New Jersey, an ethnic transition is under way. Just several decades ago, the district was a solidly Italian enclave. Today, the few remaining Italians must contend with an influx of new immigrants from Latin America. The transition from Italian to Latino has been infused with conflict that is not immediately obvious but rather lingers just under the surface. Add to this already tense situation the activities of Immigration and Customs Enforcement, which has been cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…As other scholars are increasingly demostrating (e.g., Menjívar 2021;Asad and Clair, 2017;Gómez Cervantes and Menjívar, 2020;Martínez et al, 2017), the racialization of Latinxs has consequences for their physical, behavioral, and, as we show, mental health outcomes. Rachel H. Adler (2006) notes that in the process of stereotyping Latinx individuals as undocumented, Latinx immigrants and lawful permanent residents are subjected to insults, questions, unnecessary stops, and searches based on presumed immigration status, as recent enforcement strategies have targeted groups based on their presumed likelihood of being undocumented (see Armenta 2017); that is, their social illegality (see Flores and Schachter, 2018). These findings also build on recent advances investigating the connection between the stigma of illegality and psychological wellbeing (Del Real 2019), which find that undocumented and U.S.-born Latinxs, alike, experience discrimination when they are presumed to be undocumented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As other scholars are increasingly demostrating (e.g., Menjívar 2021;Asad and Clair, 2017;Gómez Cervantes and Menjívar, 2020;Martínez et al, 2017), the racialization of Latinxs has consequences for their physical, behavioral, and, as we show, mental health outcomes. Rachel H. Adler (2006) notes that in the process of stereotyping Latinx individuals as undocumented, Latinx immigrants and lawful permanent residents are subjected to insults, questions, unnecessary stops, and searches based on presumed immigration status, as recent enforcement strategies have targeted groups based on their presumed likelihood of being undocumented (see Armenta 2017); that is, their social illegality (see Flores and Schachter, 2018). These findings also build on recent advances investigating the connection between the stigma of illegality and psychological wellbeing (Del Real 2019), which find that undocumented and U.S.-born Latinxs, alike, experience discrimination when they are presumed to be undocumented.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified a 'stigmatized Hispanic identity' from which some Latinx individuals have been shown to attempt to distance themselves (Adler 2006;Dowling and Newby, 2010). In studies conducted with samples consisting of predominantly White Americans, higher levels of prejudice were detected when immigrants were described as illegals; however, when Mexican-origin legal migrants were compared to Canadian illegal migrants, higher levels of prejudice were registered against the Mexican group (Short 2004;Short and Magaña, 2002).…”
Section: Illegality Discrimination and Psychological Distress Among Us Latinxsmentioning
confidence: 99%
“…Twenty-three percent of Trenton residents were born outside the United States, and 70% of those first-generation immigrants are Latino (U.S. Census Bureau, American Factfinder, 2010). Latinos began to arrive in Trenton in large numbers in the early 1990s and are heavily concentrated in a former-Italian enclave, Chambersburg (see Adler, 2006, for an extended discussion of Latino migration to the area). A majority of first-generation Latino immigrants in Trenton are from Guatemala (51%).…”
Section: The Current Studymentioning
confidence: 99%
“…Other individuals suspected of being undocumented may be taken as “collateral” arrests, a process rooted in racial profiling [23]. These arrests frequently include witnesses, often children [10, 14, 19, 20, 22, 24–30]. Despite the effects of these raids on health however, they have received scant attention in the health literature, often mentioned as one of many aspects of increased immigration enforcement [11].…”
Section: Introductionmentioning
confidence: 99%